2021
DOI: 10.3389/fpsyg.2021.717736
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Efficacy of ‘Unlearning’, a Mindfulness and Compassion-Based Programme for Cultivating Nonviolence in Teenagers: A Randomised Controlled Trial

Abstract: Background: Most programmes developed to reduce aggressive attitudes among teenagers are based on cultivating nonviolence, a construct that has been related to compassion and, more indirectly, mindfulness. This study aims at testing the efficacy of ‘Unlearning’, a mindfulness and compassion-based programme, for reducing aggressive attitudes in adolescents.Method: A sample of 164 students from three high schools in Zaragoza (Spain) participated in the study. They were randomly assigned to (1) ‘Unlearning’, or (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The review conducted by Lin et al [64] considered that MBIs could lead to improvement in the overall quality of life for adolescents suffering from chronic pain, but a systematic review [65] concluded that the evidence was inconsistent. Some authors have pointed out that learning mindfulness might require meta-cognitive skills that many adolescents may not have developed yet [66,67], in addition to discipline and consistency regarding meditation practice, which are also uncommon among teenagers. Thus, it is suggested that before implementing "third wave" CBT psychotherapies for adolescents with chronic pain, previous steps addressed at promoting the required basic skills should be taken.…”
Section: Discussionmentioning
confidence: 99%
“…The review conducted by Lin et al [64] considered that MBIs could lead to improvement in the overall quality of life for adolescents suffering from chronic pain, but a systematic review [65] concluded that the evidence was inconsistent. Some authors have pointed out that learning mindfulness might require meta-cognitive skills that many adolescents may not have developed yet [66,67], in addition to discipline and consistency regarding meditation practice, which are also uncommon among teenagers. Thus, it is suggested that before implementing "third wave" CBT psychotherapies for adolescents with chronic pain, previous steps addressed at promoting the required basic skills should be taken.…”
Section: Discussionmentioning
confidence: 99%